BETWEEN THE PAST AND PRESENT: FRENCH HISTORIOGRAPHY OF SCHOOL HISTORY TEXTBOOKS - Z.D., Shaimardanova (European Scientific Journal, ESJ, 2014)
French historiography reflects the key questions of the history of Kazakhstan: the global confrontation betweenthe Russian Empire - the Soviet authorities and the local population of the XIX - XX centuries, e.g. the "Accession of Kazakh steppes to the Russian”, fight of Kazakh people for the preservation of statehood and ethnic integrity etc. However, this view from this side, isoften objective. In an example, a French explorer named J. Uhrès, in an article titled: "Russian colonization in the history books of post- Soviet Central Asia" made an analysis by comparing it with textbooks on the history of Kazakhstan, published in the Soviet period and in the period of its independence. Interpretation of the key issues of national history has undergone modifications due to peculiarities of the historical development of the Russian Empire, the USSR Kazakhstan and Kazakhstan as a sovereign state.